Serum Concentrations and Gonadal Expression of INSL3 in Eighteen Males With 45,X/46,XY Mosaicism - Ljubicic, Marie Lindhardt; Jørgensen, Anne; Aksglaede, Lise; Nielsen, John Erik; Albrethsen, Jakob; Juul, Anders; Johannsen, Trine Holm (Frontiers in Endocrinology, 2021)
Objective: Insulin-like factor 3 (INSL3) is produced in the testes and has been proposed as a circulating biomarker of Leydig cell capacity, but remains undescribed in 45,X/46,XY mosaicism. The aim was to examine serum concentrations and gonadal expression of INSL3 in 45,X/46,XY mosaicism. Methods: Retrospectively collected data from medical records, gonadal tissue samples, and prospectively analyzed serum samples from eighteen male patients with 45,X/46,XY mosaicism (one prepubertal, four testosterone-treated, 13 untreated) were included. Biochemical, clinical, and histological outcomes were evaluated according to serum INSL3 concentrations, quantified by LC-MS/MS methodology, and gonadal INSL3 immunohistochemical expression. Results: Serum INSL3 concentrations spanned from below to above the reference range. In untreated patients, the median serum INSL3 SD score was -0.80 (IQR: -1.65 to 0.55) and no significant difference was observed between INSL3 and testosterone. There was no clear association between serum INSL3 and External Genitalia Score at diagnosis, spontaneous puberty, or sperm concentration. INSL3 and CYP11A1 expression overlapped, except for less pronounced INSL3 expressison in areas with severe Leydig cell hyperplasia. No other apparent links between INSL3 expression and histological outcomes were observed. Conclusions: In this pilot study, serum INSL3 concentrations ranged and seemed independent of other reproductive hormones and clinical features in males with 45,X/46,XY mosaicism. Discordant expression of INSL3 and CYP11A1 may explain low INSL3 and normal testosterone concentrations in some patients. Further studies are needed to elucidate the divergence between serum INSL3 and testosterone and the potential clinical use of INSL3.